V knjižnico s pametnim telefonom? - Traven, Eva (Šolska knjižnica, 2013)
In the past school year the library at Predoslje Primary School has been thoroughly renovated. Our desire was to make the library the central cultural facility in the school and to help the pupils navigate through the library as well as raise their reading motivation. For this reason we prepared a literary quiz using smartphones and QR codes. The goal of this activity was development of various skills and abilities of pupils, such as communication, information, research skills. Such activity is aimed at one of the curriculum goals in the course Slovenian language, namely development of digital competences which is related to the development of communication competences in the mother tongue. The pupils were highly motivated for the quiz and also acquired a lot of new skills and knowledge.
Keywords: literarni kvizi; mobilna telefonija; pametni telefoni; QR-koda; skupinsko delo; šolske knjižnice